Development of E-Module PBL Model Learning to Improve Students' Mastery of Concepts - Jumadi Jumadi; Nurfazliana Nurfazliana (Jurnal Penelitian Pendidikan IPA, 2023)
The teaching materials provided by the teacher have not been able to make students understand the material of mechanical waves. because it only contains an explanation of the material conveyed through writing. Therefore, innovative and interactive learning media are needed that are able to help students understand the concept material of mechanical wave submatter waves. This research is a type of development research (Research and Development). The development model used is the 4D model with define, design, develop and disseminate steps. This research was conducted at SMAN 1 Baitussalam in class XI students using 22 modeling field trial samples and 22 implementation field trial samples. Data collection tools were obtained from media validation questionnaires, pretest and posttest questions. The results of the validation of material and media experts show that the developed PBL-based e-module is very feasible. The N-Gain analysis shows that PBL-based e-modules are effective in increasing students' understanding of concepts. The practicality analysis results show that the e-module is very practical. Thus, the developed PBL-based e-module is suitable for use in mechanical wave learning.